The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1097/wnp.0b013e3181dd4fca
|View full text |Cite
|
Sign up to set email alerts
|

Bulbocavernosus Reflex and Pudendal Nerve Somatosensory-Evoked Potentials Responses in Female Patients With Nerve System Diseases

Abstract: To assess the value of bulbocavernosus reflex (BCR) and pudendal nerve somatosensory-evoked potential (SSEP) in the topical diagnosis of central and peripheral nervous system diseases in female patients. Neuroelectrophysiologic technique was adopted to determine both BCR and SSEP of 41 healthy adult females (control group), 30 female patients with spinal cord lesions (central group), and 50 female patients with peripheral nerve lesions (peripheral group), including nine female patients with acute cauda equina … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 7 publications
1
9
0
4
Order By: Relevance
“…Well-designed estimates of the sensitivity of free-run EMG for intraoperative nerve root injuries range from 43% (Bose et al, 2007) down to 0% (Park et al, 2011); other reports (Beatty et al, 1995;Bose et al, 2002) do not provide sufficient information to fully characterize performance. While there are reports of excellent neurophysiologic techniques to assess sacral functions (Rodi and Vodusek, 2001), and extraoperatively studied techniques of clear potential utility have been reported (Frasson et al, 2009;Niu et al, 2010), there are few systematic assessments of the utility of any techniques for any application except the identification of neural tissue for tethered cord release and/or tumor resection in the cauda equina (see chapters 52 to 55 in Nuwer, 2008, for review). What was used in the cases captured in the SRS database?…”
mentioning
confidence: 99%
“…Well-designed estimates of the sensitivity of free-run EMG for intraoperative nerve root injuries range from 43% (Bose et al, 2007) down to 0% (Park et al, 2011); other reports (Beatty et al, 1995;Bose et al, 2002) do not provide sufficient information to fully characterize performance. While there are reports of excellent neurophysiologic techniques to assess sacral functions (Rodi and Vodusek, 2001), and extraoperatively studied techniques of clear potential utility have been reported (Frasson et al, 2009;Niu et al, 2010), there are few systematic assessments of the utility of any techniques for any application except the identification of neural tissue for tethered cord release and/or tumor resection in the cauda equina (see chapters 52 to 55 in Nuwer, 2008, for review). What was used in the cases captured in the SRS database?…”
mentioning
confidence: 99%
“…In our previous studies, the BCR test has already been shown to be a highly sensitive and specific detection method for the diagnosis of nervous system diseases in adult male and female populations in China [12-15]. Normal BCR performance has also been established for Chinese male and female subjects, with significant differences in BCR latency between the sexes [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…15 Therefore, in this study, we examined BCR and PSEPs in patients with MSA and PD, looking for distinguishing hallmarks that might be useful in the differential diagnosis, especially in the early stages of these two disorders. 14 Measurement of pudendal nerve somatosensory evoked potentials (PSEPs) is an objective neurophysiological assessment method for evaluating the entire pudendal nerve afferent pathway.…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…14 Measurement of pudendal nerve somatosensory evoked potentials (PSEPs) is an objective neurophysiological assessment method for evaluating the entire pudendal nerve afferent pathway. 15 Therefore, in this study, we examined BCR and PSEPs in patients with MSA and PD, looking for distinguishing hallmarks that might be useful in the differential diagnosis, especially in the early stages of these two disorders.…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%